2019
DOI: 10.1002/ecj.12208
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of refractive index sensors using polarization independent metamaterial and their application to chemical concentration measurement and DNA detection

Abstract: Biochemical sensors are used for discrimination of biochemical species, concentration measurement, and so on. Because metamaterial responds to slight changes in the ambient refractive index, it is possible to realize ultrasensitive biochemical sensors. We designed and fabricated refractive index sensors using polarization independent metamaterial and examined their application as biochemical sensors. Refractive index sensitivity, concentration measurement, and DNA detection were carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Next, the target DNA with a completely complementary sequence to the sensor DNA was added and washed with pure water, and then, the reflection spectrum in a dry state was measured. Figure 11 shows a comparison of reflection spectra before and after DNA binding [119]. As shown in the figure, it was confirmed that the reflection peak of the metamaterial was shifted by 8.5 nm due to the binding of the target DNA, and the DNA could be detected.…”
Section: Application Of Nanophotonic Optical Filtersmentioning
confidence: 79%
See 3 more Smart Citations
“…Next, the target DNA with a completely complementary sequence to the sensor DNA was added and washed with pure water, and then, the reflection spectrum in a dry state was measured. Figure 11 shows a comparison of reflection spectra before and after DNA binding [119]. As shown in the figure, it was confirmed that the reflection peak of the metamaterial was shifted by 8.5 nm due to the binding of the target DNA, and the DNA could be detected.…”
Section: Application Of Nanophotonic Optical Filtersmentioning
confidence: 79%
“…However, the refractive index sensitivity is inferior to that of the refractive index sensor [135] reported by Lee et al In recent years, the author has designed and fabricated a localized surface plasmon-type refractive index sensor using a polarization-independent metamaterial with the aim of realizing a compact and highly sensitive biochemical sensor [116,119]. Figure 10 shows an SEM photograph of the metamaterial fabricated by the author [119]. Au cut wire structures are formed rotationally symmetrically on a quartz substrate.…”
Section: Application To Dna Detection By a Highsensitivity Refractivementioning
confidence: 99%
See 2 more Smart Citations